Reflections on work and capital - Flores, Humberto (Teoría y Praxis, 2022)
This article aims to present some reflections on Wage-Labor and Capital based on Ignacio Ellacuría’s work: “El conflicto entre el trabajo y el capital en la presente fase histórica, un análisis de la encíclica del Papa Juan Pablo II sobre el trabajo humano”, 1982; “El mal común y los derechos humanos”, 1989 and “Utopía y profetismo desde América latina”, 1989. Carl Marx’s thought will also be included in relation to the topic discussed. Finally, these concepts will be applied to the current context, characterized by a clear global financial crisis.